Effects of liposomal form of phosphatidylcholine on oxidative-nitrosative stress in renal tissues of rats in burn disease - Ya. O. Basarab; L. H. Netyukhailo (Kazimierz Wielki University, 2020)
This experiment carried out on 77 white Wistar rats aimed at studying the effects of liposomal form of phosphatidylcholine (lipin) on oxidative-nitrosative stress in renal tissues in burn disease (BD). This condition was modelled by immersing the epilated skin surface of the hind limb of the experimental animals into hot water (t + 70 -75°C) under light ether anaesthesia for 7 s that led to the development of III A-B degree burns. Lipin was administered intraperitoneally daily in a dose of 50 mg / kg immediately after BD modelling. The research has demonstrated BD modelling is accompanied by the development of oxidative-nitrosative stress in renal tissues as evidenced by a significant increase in the superoxide anion radical production by various sources (endoplasmic reticulum and NO synthase, mitochondrial respiratory chain, leukocyte NADPH oxidase); by the growth in the activity of inducible isozyme of NO-synthase (in the stage of burn shock in 2.83 times, р<0.001) with a decline in the constitutive isoforms activity, by the rise in the concentration of peroxynitrite (in the stage of burn shock in 3.18 times, in the stage of septicotoxemia in 2.56 times). The administration of lipin significantly limits the development of oxidative-nitrosative stress in renal tissues in the dynamics of experimental BD, as evidenced by a probable decrease in superoxide anion radical, NO-synthase activity due to its inducible isoform (in the stage of burn shock - by 35.9%; in the stage of toxemia - by 43.1%, p<0.001), by redressing the imbalance between inducible and constitutive isozymes of NO-synthase, by reducing the concentration of peroxynitrite (in the stage of burn shock - by 34.3%, in the stage of late toxemia - by 44.3%; in the stage of septicotoxemia - by 44.3%, p<0.001).